Development of laminated bamboo lumber with high bond strength for structural uses by O2 plasma. (1st February 2021) - Wu, Jianfei; Yuan, Hongmei; Wang, Wei; Wu, QiRong; Guan, Xin; Lin, Jinguo; Li, Jiqing
Graphical abstract: Highlights: The volume utilization rate of bamboo residues is more than 85%. The O2 plasma modification time is 6min, the wet bonding strength is increased by 75.69%. The staggered arrangement of bamboo pieces in LBL can reduce the influence of anisotropy. After O2 plasma modification, the wettability of bamboo was improved obviously. Abstract: To improve the reuse rate of bamboo materials, laminated bamboo lumber (LBL) with high bond strength has been developed for structural use using bamboo residues (BRs). The laminated structure design is an important factor affecting LBL performance, and thus, it is essential to study various LBL blank structures. The major direction is parallel to the panel length, and the minor direction is perpendicular to the panel length. In this study, BRs were cut into A and B units along the major and minor directions, respectively. The LBL with good performance was selected by different forming methods and modified by O2 plasma. It was found that 1) the volume utilization rate of BRs in LBL is above 85%; 2) the wet bonding strength of LBL products is increased by 58.58% compared to ordinary plywood, when the O2 plasma modification time is 6 min and 12 min respectively, the wet bonding strength is increased by 75.69% and 76.27% compared to ordinary plywood; 3) when bamboo pieces are arranged in parallel, the modulus of rupture in the major direction is ~ 2 times greater than in the minor direction, while a staggered arrangement can effectively reduce the bamboo anisotropic effect; 4) the destruction of LBL mainly occurs at the joints; 5) after O2 plasma modification, the wettability of green bamboo and yellow bamboo was significantly improved, followed by bamboo flesh.